Improving Student Learning at SMAN 2 Regarding the General Ledger and Trial Balance Worksheets - Chelsya Chelsya (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This community service program aimed to improve students’ accounting literacy and practical skills in general ledger posting and trial balance worksheet preparation at SMAN 2 West Jakarta. The program was designed to bridge the gap between theoretical accounting learning in school and practical competencies required in the workplace. Method: The activity was conducted at SMAN 2 West Jakarta on May 13, 2026, for students of Class XI-4. The intervention involved accounting education, hands-on practice, case-based simulations, and digital evaluation using Quizziz and Google Forms. The training covered the concepts, functions, and procedures of posting transactions to the general ledger and preparing trial balance worksheets. Results and Discussion: Prior to the intervention, students had limited practical understanding of the accounting cycle, particularly in general ledger posting and trial balance worksheet preparation. The activity was implemented in chronological order: introduction, pre-test, material presentation, guided practice, post-test, and participant satisfaction evaluation. The results showed improved student understanding, with a post-test average score of 81. Participants also demonstrated increased engagement, motivation, and ability to complete accounting practice exercises with guidance. Implications: This program helped strengthen students’ basic accounting competencies and work readiness. Future community service programs should provide longer training and cover a broader range of accounting topics, including financial statement preparation, tax literacy, digital finance, and sustainability reporting.